An architecture for a configurable mixed-signal device. - Mar, M.
The mixed-signal programmable system-on-chip (PSOC) architecture for high-volume low-cost applications is presented. Programmable analog, digital, and clocking circuits are combined with flash memory and a microcontroller to provide a platform for single-chip solutions for low-cost consumer applications. Both programmable analog and digital circuits are designed to support a moderate level of abstraction, balancing flexibility against cost and performance. A rough comparison of alternative approaches based on functionality and cost is presented.
Keywords: PSOC; Clocking circuits; Configurable mixed-signal device; Consumer applications; Flash memory; Flexibility; Low-cost applications; Microcontroller; Programmable system-on-chip.; Single-chip solutions